2019
DOI: 10.1371/journal.pone.0226245
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery of a modified antibody to Aβ reduces progression of murine Alzheimer’s disease

Abstract: Antibody therapies for Alzheimer’s Disease (AD) hold promise but have been limited by the inability of these proteins to migrate efficiently across the blood brain barrier (BBB). Central nervous system (CNS) gene transfer by vectors like adeno-associated virus (AAV) overcome this barrier by allowing the bodies’ own cells to produce the therapeutic protein, but previous studies using this method to target amyloid-β have shown success only with truncated single chain antibodies (Abs) lacking an Fc domain. The Fc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…FcR-mediated endocytosis [28,[43][44][45][46], internalisation mediated by electrostatic interactions with the plasma membrane [47] and through lipid rafts on the surface of the plasma membrane [48]. However, neurons are not specialised to express nor do they cope well with high intracellular concentrations of IgG, as has been shown by Elmer and colleagues, where viralmediated expression of IgG antibodies resulted in glycoprotein accumulation and subsequent neuronal degeneration [49]. While RNF5 was not expressed intracellularly in our study, it is possible that forcing large amounts of IgG into cells can be detrimental to neuronal health due to neurons being incapable of processing large quantities of glycoprotein.…”
Section: Igg Internalisation Into Neurons Has Been Shown To Occur Via...mentioning
confidence: 99%
“…FcR-mediated endocytosis [28,[43][44][45][46], internalisation mediated by electrostatic interactions with the plasma membrane [47] and through lipid rafts on the surface of the plasma membrane [48]. However, neurons are not specialised to express nor do they cope well with high intracellular concentrations of IgG, as has been shown by Elmer and colleagues, where viralmediated expression of IgG antibodies resulted in glycoprotein accumulation and subsequent neuronal degeneration [49]. While RNF5 was not expressed intracellularly in our study, it is possible that forcing large amounts of IgG into cells can be detrimental to neuronal health due to neurons being incapable of processing large quantities of glycoprotein.…”
Section: Igg Internalisation Into Neurons Has Been Shown To Occur Via...mentioning
confidence: 99%
“…Other gene therapy approaches attempt to produce antibodies against β-amyloid. 254 Focal transgene expression (ie, in the proximity of amyloid plaques), has been investigated in mouse models of AD 255 …”
Section: Potential Strategies To Combat Ad Based On Modifying the Act...mentioning
confidence: 99%
“…Other gene therapy approaches attempt to produce antibodies against β-amyloid. 254 Focal transgene expression (ie, in the proximity of amyloid plaques), has been investigated in mouse models of AD 255 Multimodal AD therapy includes gliotherapy Many different approaches have been considered to fight against AD (neuronal defense/repair, gliotherapies, AD preventive approaches) (Figure 1). Pharmacological and nopharmacological therapies have been proposed.…”
Section: New Gene Neuroglial Therapiesmentioning
confidence: 99%
“…As a way of addressing these issues, Elmer et al ( 2020) [36] performed intrahippocampal injections of an AAV vector encoding a transcript for anti-Aβ IgG into 2-month-old APP mutation mice, just prior to the time of Aβ plaque deposition in this model. They found that CNS expression of anti-Aβ IgG was maintained at levels higher than peak concentration achieved with IV injection and that it resulted in reduced cortical and hippocampal Aβ load.…”
Section: Aβ/appmentioning
confidence: 99%